2017
DOI: 10.1007/s40279-017-0723-1
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Promote Fundamental Movement Skills in Childcare and Kindergarten: A Systematic Review and Meta-Analysis

Abstract: BackgroundProficiency in fundamental movement skills (FMS) lays the foundation for being physically active and developing more complex motor skills. Improving these motor skills may provide enhanced opportunities for the development of a variety of perceptual, social, and cognitive skills.ObjectiveThe objective of this systematic review and meta-analysis was to assess the effects of FMS interventions on actual FMS, targeting typically developing young children.MethodSearches in seven databases (CINAHL, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
166
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(187 citation statements)
references
References 109 publications
(473 reference statements)
11
166
1
9
Order By: Relevance
“…Most importantly, they could have a firm grasp of the fundamental movement skills and being physically literate leads a child to enjoy a long life of physical activity (Wick et al, 2017).…”
Section: It Is Important Firstly To Define What Fundamental Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, they could have a firm grasp of the fundamental movement skills and being physically literate leads a child to enjoy a long life of physical activity (Wick et al, 2017).…”
Section: It Is Important Firstly To Define What Fundamental Movementmentioning
confidence: 99%
“…FMS are essential to the more specialized and complex skills used in playing, games, and sports. Mastery of these basic motor skills that predominantly evolve during the preschool years , is an essential part of pleasant participation and a lifelong interest in a physically active lifestyle (Wick et al, 2017).…”
mentioning
confidence: 99%
“…FMS consist of two main categories: locomotor skills involving the movement of the body via space (e.g., running and galloping) and object control skills requiring hands and feet to manipulate an object (e.g., throwing and catching) [2]. FMS underscore specific and complex motor skills in varied activities across the lifespan [3]. Previous studies have demonstrated that sufficient FMS competence is associated with increased physical activity and improved health status over one's lifetime [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Wick et al (2017) conducted a systematic review and meta-analysis on interventions to promote fundamental movement skills in childcare. They implicate that "fundamental movement skills should and can be taught in childcare" [25]. The problem of low motor skills in young children still seems to be urgent.…”
Section: Introductionmentioning
confidence: 99%